Carga laboral y nivel de estrés en enfermeros (as) por COVID-19 en el Hospital Virgen de la Puerta, Trujillo - Becerra Mayta, Marilyn Cecilia (2022)
The research entitled "Workload and stress level in nurses by COVID-19 in the Hospital Virgen de la Puerta, Trujillo" had the objective of describing the relationship between workload and stress level in nurses by COVID-19 in the Hospital Virgen de la Puerta, Trujillo, following the theories of Florence Nightingale in relation to the environment and Selye's stress theory linked to health, which were the basis for this study. The research methodology was quantitative, descriptive-correlation, non-experimental-cross sectional approach. The research population consisted of 100 nurses and the sample consisted of 66 of them. The technique was the survey through social networks and the instrument was the questionnaire, which allowed the collection of data that were later analyzed through descriptive statistics and inferential statistics, the latter establishing Kendall's Tau b test as a factor of analysis. The results of the study were that 18.2% of the nurses of the Hospital de Alta Complejidad Virgen de la Puerta presented a low level of workload per COVID-19, 42.4% a medium level of workload and 39.4% a high level of workload, in addition; 9.1% of the nurses presented a low level of stress, 19.7% a medium level of stress and 71.2% a high level of stress. It was concluded in the research that workload has a significant relationship with the level of stress in nurses of the Hospital de Alta Complejidad “Virgen de la Puerta” [0.301, p<0.0015] accepting the alternative hypothesis.